Concentrated Growth Factor (CGF) in Alveolar Bone Grafting Procedures: Dilemma or Reality? - A Commentary (Global Journal of Medical Research, 2019)
Alveolar bone grafting is considered to be one of the most challenging task in the management of cleft lip and palate patients as it is expected to bridge the gap between the alveolar segments and provide the solid base for the un-erupted tooth/teeth to erupt through it, besides effectively healing the Oro-antral fistula if any passing through the cleft into the nasal cavity. Although the traditional approach is to use autogenous bone graft from iliac crest, which has its own side-effects like pain, morbidity, additional surgery, etc.
Keywords: concentrated growth factors; platelet-rich plasma; autologous bone; alveolar bone grafting; osteogenic potential